Kinetic isotope effects in methane coupling on a reducible oxide catalyst - Burch, R; Tsang, S; Mirodatos, C; Sanchez M, J (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1990)
Kinetic isotope effects in methane activation on a reducible Na/MnOx/SiO2 catalyst have been investigated. The results show that there is a kinetic isotope effect for the formation of C2 products but not for the formation of COx, products. These observations conflict with kinetic measurements of the rate of formation of C2 products which appear to show that the reaction is second order with respect to the methane partial pressure. It is concluded that the rate determining step is activation of the C-H (or C-D) bond and that the apparent second order kinetics is an artefact of the kinetic analysis. The absence of a kinetic isotope effect in the formation of carbon oxides is discussed. © 1991 J.C. Baltzer A.G. Scientific Publishing Company.